Diversity of endophytic fungi isolated from different plant parts of Acacia mangium, and antagonistic activity against Ceratocystis fimbriata, a causal agent of Ceratocystis wilt disease of A. mangium in Malaysia - Ahmad, Mohd Farid; Zahari, Rozihawati; Mohtar, Mastura; Wan-Muhammad-Azrul, Wan Azhar; Hishamuddin, Muhammad Syahmi; Samsudin, Nik Iskandar Putra; Hassan, Affendy; Terhem, Razak (Frontiers in Microbiology, 2022)
Acacia mangium is an important wood for commercial products especially pulp and medium-density fibreboard. However, it is susceptible to Ceratocystis fimbriata infection, leading to Ceratocystis wilt. Therefore, the present work aimed to (i) establish the diversity of endophytic fungi in different plant parts of A. mangium, (ii) evaluate the antifungal potentials of the isolated and identified endophytic fungi against C. fimbriata, and (iii) evaluate the antibacterial potentials of the isolated and identified endophytic fungi against common foodborne/human pathogens. Endophytic fungal identification was conducted by PCR amplification and sequencing of the internal transcribed spacer 1 (ITS1) and ITS4 regions of nuclear ribosomal DNA. A total of 66 endophytic fungi were successfully isolated from different parts of A. mangium; leaf (21), stem (13), petiole (12), root (9), flower (6), and fruit (5). The endophytic fungal isolates belonged to Ascomycota (95.5%) and Zygomycota (4.5%). Of the Ascomycota, 13 genera were identified; Trichoderma (28.6%), Nigrospora (28.6%), Pestalotiopsis (12.7%), Lasiodiplodia (9.5%), Aspergillus (6.3%), Sordariomycetes (3%), and Neopestalotiopsis, Pseudopestalotiopsis, Eutiarosporella, Curvularia, Fusarium, Penicillium, and Hypoxylon each with a single isolate. For Zygomycota, only Blakeslea sp. (5%) was isolated. Against C. fimbriata, Trichoderma koningiopsis (AC 1S) from stem, Nigrospora oryzae (AC 7L) from leaf, Nigrospora sphaerica (AC 3F) from flower, Lasiodiplodia sp. (AC 2U) from fruit, Nigrospora sphaerica (AC 4P) from petiole, and Trichoderma sp. (AC 9R) from root exhibited strong inhibition (58.33 – 69.23%). Against bacterial pathogens, crude extracts from Trichoderma spp., N. sphaerica, and Lasiodiplodia sp. inhibited the three Gram-positive bacteria (Staphylococcus aureus, methicillin-resistant S. aureus, Bacillus subtillis) with low MIC and MBC values, ranging from 0.313 to 1.25 µg/µL, but not the Gram-negative bacteria (Escherichia coli, Pseudomonas aeruginosa). Thus, it can be concluded that certain endophytic fungi of A. mangium has the potential to be harnessed as anti-Ceratocystis and antibacterial agents in future biotechnological applications.